Leadership : limits and possibilities - Grint, Keith (Houndmills, Basingstoke, Hampshire ; New York, N.Y. : Palgrave Macmillan, 2005)
'Leadership' provides a critical review & analysis of the key components of leadership: the foundations of good leadership, the relationship between leaders & subordinates, & the roles leaders play in the dynamics of organisational life.
CONTENTS: Introduction.- What is Leadership: Person, Result, Position or Process?.- Leadership as Person: Putting the "Ship" Back into Leadership.- Leadership as Results: Putting the Subjunctive Back Where it Belongs.- Leadership as Process: Leadership as a Reflection of Community.- Leadership as Position: Hydras and Elephants.- Bibliography.- Index.
Includes bibliographical references (p. 166-178) and index.
Keywords: Executive ability; Leadership; Organizational effectiveness